2022
DOI: 10.1088/1361-6668/ac7dfe
|View full text |Cite
|
Sign up to set email alerts
|

Study on current discrepancy and redistribution of HTS non-insulation closed-loop coils during charging/discharging and subsequent transient process toward steady-state operation

Abstract: It has been previously demonstrated that currents in HTS non-insulation (NI) coils exhibit a discrepant distribution during charging and discharging. However, for NI closed-loop coils, novel phenomenons that arose from the current discrepancy have not been fully studied, especially during transient processes after charging and discharging, or more strictly speaking, after the persistent current switch returns to the superconducting state. For example in our project of a prototype maglev system, a rapid decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(22 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…For the precise charging of NI closed-loop coils, a charging strategy using PCS and the flux pump was proposed [51]. This work experimentally proved the possibility of the NI HTS coil excitation scheme using a combination of PCS/external power supply and the flux pump.…”
Section: Hts Coil Excitation Experimentsmentioning
confidence: 73%
See 2 more Smart Citations
“…For the precise charging of NI closed-loop coils, a charging strategy using PCS and the flux pump was proposed [51]. This work experimentally proved the possibility of the NI HTS coil excitation scheme using a combination of PCS/external power supply and the flux pump.…”
Section: Hts Coil Excitation Experimentsmentioning
confidence: 73%
“…The basic performance of the linear flux pump was discussed in section 3. To verify the practical application of the miniaturized flux pump, it was connected to an HTS racetrack coil for a maglev project [51]. The racetrack coil was excited.…”
Section: Hts Coil Excitation Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors did not avoid the non-uniform ρ t2t for this NI coil sample even though this sample is well-wound with constant pre-stress and strongly compacted with the Kapton over-banding. In previous experiments, Lu et al have derived the non-uniform ρ t2t distribution that the innermost and outermost turns have the largest ρ t2t values through refined voltage measurements for different sections of their NI coil [61]. Wang et al have found that experimental results agree better with the simulation results setting larger ρ t2t value for the outermost turns [62].…”
Section: Simulation Analysismentioning
confidence: 99%
“…Additionally, the alternating background magnetic field also induces radial currents in the NI coils or similar cables, which leads to inter-turn losses [18,19], distinct dynamic resistance distribution from the insulated coils [20][21][22], and the redistribution of coil currents and spatial magnetic fields [23]. In closed-loop NI coils during the excitation process, non-uniform distribution of circumferential and radial currents and their continuous redistribution processes will be experienced after turning the persistent current switch to be superconducting and lead to a misunderstanding of the field decay rate [24]. In this condition, accurate prediction of the operating current at stable persistent current mode is significantly affected by TTRD.…”
Section: Introductionmentioning
confidence: 99%